Predictive factors for sperm retrieval and sperm injection outcomes in obstructive azoospermia: do etiology, retrieval techniques and gamete source play a role? (Clinics, 2013)
Obstructive azoospermia is a relatively common male infertility condition. The main etiologies of obstructive azoospermia include congenital, surgical-derived, traumatic and post-infectious cases. Although seminal tract reconstruction is a cost-effective treatment in most cases, this approach may not be feasible or desired in some cases. In such cases, assisted reproduction techniques offer a method for achieving pregnancy, notably via sperm retrieval and intracytoplasmic sperm injection. This process requires several considerations and decisions to be made, including the cause and duration of obstruction, which sperm retrieval technique to use, and whether to use fresh or frozen-thawed sperm. We present a review of obstructive azoospermia and assisted reproduction techniques, highlighting the most relevant aspects of the decision-making process for use in clinical practice.